Adaptive ultimate load analysis of RC shells - Lackner, Roman; Mang, Herbert A. (Computer Assisted Methods in Engineering and Science, 2023)
The aim of the present paper is a synthesis of both realistic modelling of the structural behavior of reinforced concrete (RC) shells and an adaptive finite element (FE) calculation tool suitable for the solution of nonlinear problems involving strain-hardening and softening plasticity. In the context of incrementaliterative analysis, an incremental error estimator is introduced. It is based on the rate of work. The reference solution required for error estimation is obtained by means of a recovery scheme applied to stress resultants. If the estimated error exceeds a prespecified threshold value, a new mesh is designed. Mesh generation is performed in the 2D parametric space of the shell. After mesh refinement, the state variables are transferred from the old to the new mesh and the calculation is restarted at the load level which was attained by the old mesh. The usefulness of the developed adaptive analysis scheme is demonstrated by a numerical analysis of an RC cooling tower.